Martial law melodrama Lino Brocka's cinema politics - Capino, Jose B. (Ateneo de Manila University Press, 2023)
"Lino Brocka (1939-1991) was one of Asia and the Global South's most celebrated filmmakers. A versatile talent, he was at once a bankable director of genre movies, an internationally acclaimed auteur of social films, a pioneer of queer cinema, and an outspoken critic of Ferdinand Marcos's autocratic regime. José B. Capino examines the figuration of politics in the Filipino director's movies, illuminating their historical contexts, allegorical tropes, and social critiques. Combining eye-opening archival research with fresh interpretations of over fifteen of Brocka's major and minor works, Martial Law Melodrama does more than reveal the breadth of his political vision. It also offers a timely lesson about popular cinema's vital role in the struggle for democracy"